Faktor Penyebab Burnout Syndrome pada Pekerja Kantor: Literature Review - Carissa Dar Azizi; Endang Dwiyanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Burnout syndrome is a complex condition of work-related exhaustion involving physical, emotional, and mental aspects resulting from prolonged exposure to occupational stress and is increasingly experienced by office workers due to rising job demands and the dynamics of modern organizations. Burnout is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, which negatively affect employee performance and well-being. This study aims to examine the factors contributing to burnout syndrome in office work settings through a literature review approach. Article searches were conducted using the Google Scholar database with inclusion criteria of publications within the last five years, availability of full-text articles, and relevance to burnout among workers, and were selected using PRISMA guidelines. The synthesis results indicate that burnout among office workers is influenced by high job demands and workload, inadequate work environments and organizational support, as well as individual factors such as age, gender, emotional intelligence, and personal sense of responsibility. These findings suggest that burnout is a multidimensional phenomenon arising from the interaction of job-related, organizational, and individual factors. Therefore, organizations should manage workloads proportionally and strengthen supervisory support and worker-friendly work environments, while employees should be equipped with stress management skills and strategies to maintain work–life balance to prevent burnout syndrome.